2020
DOI: 10.1021/acssuschemeng.0c01016
|View full text |Cite
|
Sign up to set email alerts
|

Novel Processing for Color-Tunable Luminescence Carbon Dots and Their Advantages in Biological Systems

Abstract: The novel strategy for color-tunable carbon dots (CDs) with superior dispersibility in an aqueous solution is originally proposed in a one-pot hydrothermal method. The optimized emission of resulted CDs progressively shifts from green to red with the adjustment of precursor solution from alkali to acid. The proposed three representative CDs entire green, yellow, and red fluorescences prepared separately on alkaline, neutral, and acidic aqueous solutions possess similar graphite structures in their carbon cores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…Because of the outstanding merits of CDs including superior optical properties, high photostability, robust chemical inertness, low toxicity, excellent biocompatibility, facile preparation, and easy modification, they have aroused tremendous research interest. Particularly, they are regarded as one of the most promising nanomaterials for fluorescent sensors, , drug delivery, photocatalysis, bioimaging, and optoelectronic devices. Great efforts have been made by scientists to improve the fluorescence quantum yield (QY) of CDs, and now, thousands of precursors have been reported for the synthesis of CDs by several different synthetic approaches such as hydro-/solvothermal synthesis assay, laser ablation, pyrolysis, ultrasonication, microwave treatments, electrochemical oxidation, and so on. However, most of the prepared CDs emitted blue or green fluorescence under ultraviolet excitation, which distinctly restricts their applications, especially in fluorescence imaging, as the blue autofluorescence of biological matrixes could mask the signal of CDs and UV light irradiation could also cause photodamage to cells and tissues. , One approach to overcome this problem is to shift the wavelength of CDs to the red or near-infrared region, where cells have weaker autofluorescence. Therefore, CDs with red or near-infrared emission are more suitable for bioimaging. Another motivation for synthesizing red-emission CDs (R-CDs) is that red phosphor is one of the primary tricolors for fabricating full-color-emitting and display devices.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the outstanding merits of CDs including superior optical properties, high photostability, robust chemical inertness, low toxicity, excellent biocompatibility, facile preparation, and easy modification, they have aroused tremendous research interest. Particularly, they are regarded as one of the most promising nanomaterials for fluorescent sensors, , drug delivery, photocatalysis, bioimaging, and optoelectronic devices. Great efforts have been made by scientists to improve the fluorescence quantum yield (QY) of CDs, and now, thousands of precursors have been reported for the synthesis of CDs by several different synthetic approaches such as hydro-/solvothermal synthesis assay, laser ablation, pyrolysis, ultrasonication, microwave treatments, electrochemical oxidation, and so on. However, most of the prepared CDs emitted blue or green fluorescence under ultraviolet excitation, which distinctly restricts their applications, especially in fluorescence imaging, as the blue autofluorescence of biological matrixes could mask the signal of CDs and UV light irradiation could also cause photodamage to cells and tissues. , One approach to overcome this problem is to shift the wavelength of CDs to the red or near-infrared region, where cells have weaker autofluorescence. Therefore, CDs with red or near-infrared emission are more suitable for bioimaging. Another motivation for synthesizing red-emission CDs (R-CDs) is that red phosphor is one of the primary tricolors for fabricating full-color-emitting and display devices.…”
Section: Introductionmentioning
confidence: 99%
“…7B). 67 They demonstrated that the CDs synthesized under alkaline conditions have stronger oxidation resistance and the amino groups on the p -PD precursor are more easily activated under acidic conditions, which results in in-depth cross-linking and facilitates a long wavelength emission. Moreover, the pursuit of developing intense emissions in the far-red and near-infrared regions (>600 nm) is attracting increasing attention owing to their superior properties, such as minimum tissue absorption, deep tissue penetration, low interference from auto fluorescence, and minimal photo damage from far-red and NIR light to biological samples.…”
Section: Various Precursor-derived Cdsmentioning
confidence: 99%
“…Having established the physical characteristics of the Bio-CDs, we next systematically investigated their optical properties, including UV-vis absorption, photoluminescence (PL) excitation, PL emission, PL decay and PL stability (Figure 2). The UV absorption spectrum of an aqueous solution of Bio-CDs showed a strong absorption peak at ~300 nm and a shoulder peak at 345 nm (Figure 2A), which were attributed to π-πp transitions of C=C and n-πp transitions of C=O/C=N bonds, respectively (Jiang et al, 2020;Jiao et al, 2020;Wei et al, 2020). In the PL spectrum of an aqueous solution of Bio-CDs (Figure 2B), the emission wavelength gradually shifted from 427 to 491 nm as the excitation wavelength was increased from 330 to 430 nm.…”
Section: Optical Properties Of Bio-cdsmentioning
confidence: 99%